Network code assisted HARQ scheme in multi-user systems with cooperative relays. (6th June 2011) - Cheung, Chun; Cheng, Roger S.
A network code assisted HARQ system considering uplink (UL) transmission with multiple mobile stations (MSs) cooperating with a relay-station (RS) is proposed. The RS is assumed to successfully monitor and decode the packets transmitted from the MSs to the base station (BS). The BS partitions the incorrectly decoded packets into groups based on their MS-to-BS channel conditions and feedbacks this partition to the RS. The RS employs a network-coded HARQ scheme within each group for subsequent retransmissions. We proposed a dynamic and adaptive partitioning method based on the BS channel state information and the corresponding HARQ retransmission schemes. Also, we derived a low-complexity joint demodulation and decoding structure. Simulations showed that our scheme improves the system throughput by 15% when compared with the relay assisted chase-combining HARQ system. We also explored suitable ranges of diversity orders for the RS-to-BS and MS-to-BS channels that provide significant system throughput improvements with practical implementation cost.